PENGARUH KUALITAS KEHIDUPAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PENERBANG DAN CREW PESAWAT POLRI PADA DIREKTORAT POLUDARA KORPOLAIRUD BAHARKAM POLRI - Asep Tapip Yani; Fira Andarini (Sekolah Tinggi Manajemen IMMI, 2019)
This study aims to determine the extent of the influence of work life quality and work motivation on the performance of pilots and crew of the Indonesian National Police at the Police Directorate of Korpolairud Baharkam Polri. and to test whether motivation is the most dominant variable influencing the performance of pilots’ performance and crew of the Indonesian National Police at the Police Directorate of the Korpolairud Baharkam Polri. To analyze the descriptive analysis method, multiple regression analysis and hypothesis testing were used. The results of the research show that from the results Based on the results of the regression coefficient analysis, the regression equation is obtained for the three variables, namely: There is a positive and significant effect on the quality of work life on the performance of the Indonesian Air Force Polar Aviation Crew and Aircraft Corps. t count test is 2,272 with a significance of 0.029. There is a positive and significant influence between work motivation on the performance of Aviation and Polri Aircraft Crew at the Police Directorate of the Police Corps of Baharkam Polri. This is shown from the results of the t test of 2,398 with a significance of 0.022.There is a significant effect between the quality of work life and work motivation on the performance of the Indonesian Air Force’s Flight Crew and Aircraft at the Police Directorate of the Police Corps of the Indonesian Police Corps. This is indicated by the results of the calculated F test of 5,169 with a significance of 0,000 and the regression equation Y = -5,607 + 0.335X1 + 0.750X.